2012
DOI: 10.1002/elan.201200052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carbon Paste Electrode Modified with Biomass for Studying the Equilibria, Kinetics, and Proton Exchange Processes Associated with Bioaccumulation

Abstract: The sorption of Cd2+ onto nonliving Typha latifolia roots was investigated using carbon paste electrodes modified with a powder formed from the ground dried root. The equilibria, kinetics, and proton exchange processes associated with the biosorption process were determined. Cd2+ was found to accumulate on the root‐modified electrode under open circuit conditions, and the electrode was transferred to an electrochemical cell for square wave anodic stripping voltammetry measurements. The measured currents were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…After this, the electrode was rinsed with water and transferred to a solution containing only support electrolyte (NaClO 4 0.1 mol L −1 ). Square wave anodic stripping voltammetry (SWASV) experiments were carried out, and a deposition potential (E dep ) of −0.75 V was applied during 120 s for Cd 2+ , while for Tl + E dep was −0.8 V and was applied for 60 s. These conditions were obtained in earlier works for Cd 2+ , 19 and obtained experimentally for Tl + . For both ions, a square wave with a frequency of 10 Hz, amplitude of 0.02 V, and potential step size of 0.004 V was applied at a range of −1.2 to 0.2 V. All experiments were performed in triplicate, and the standard deviation was calculated.…”
Section: Electrochemical Experimentsmentioning
confidence: 82%
See 1 more Smart Citation
“…After this, the electrode was rinsed with water and transferred to a solution containing only support electrolyte (NaClO 4 0.1 mol L −1 ). Square wave anodic stripping voltammetry (SWASV) experiments were carried out, and a deposition potential (E dep ) of −0.75 V was applied during 120 s for Cd 2+ , while for Tl + E dep was −0.8 V and was applied for 60 s. These conditions were obtained in earlier works for Cd 2+ , 19 and obtained experimentally for Tl + . For both ions, a square wave with a frequency of 10 Hz, amplitude of 0.02 V, and potential step size of 0.004 V was applied at a range of −1.2 to 0.2 V. All experiments were performed in triplicate, and the standard deviation was calculated.…”
Section: Electrochemical Experimentsmentioning
confidence: 82%
“…In earlier works, our work team has proposed the use of carbon paste electrodes modified with biomass. 18,19 With this method the electrode modified with biomass is exposed to a solution containing the ion studied, and the ion fixed to the electrode through biomass is analyzed by electrochemical techniques. This methodology has the advantage of requiring a small quantity of biomass and reagents moreover the time used for experiments is considerably smaller than the batch studies.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks observed at −0.82 V and at 0.15 V from CPEM corresponded to Cd(II) and Cu(II) reduction, respectively, because of the nature of the potential sequences applied ( Figure 7 ). Since the signal is generated by the electron transfer on this particular CPEM surface, any potential shift from the standard value could be explained not only by the surface used but also by strong metal- P. veronii 2E binding ( Martínez-Sánchez et al, 2012 ). Since no peaks were observed at those potentials on the CPE surface, the occurrence of electric signals was derived from P. veronii 2E-metal biosorption onto the bacterial-modified electrode surface.…”
Section: Discussionmentioning
confidence: 99%
“…biosorption-based biosensor was developed with a lineal range from 0.5 to 10 μM ( Alpat et al, 2008 ) and a Rhodotorula mucilaginosa modified microbial sensor with a lineal range from 0.1 to 10 μM ( Yüce et al, 2010 ). For Cd(II) detection a Typha latifolia root-modified CPE was characterized ( Martínez-Sánchez et al, 2012 ). Devnani et al (2014) reported a black rice extract-CPE for Pb(II), Cd(II), Cu(II), and Zn(II) detection.…”
Section: Introductionmentioning
confidence: 99%